Multi-scale analysis of fracturing characteristics of coalbed methane wells in Tunlan Block - Hongyu LI; Xiaoxia SONG; Wei LIU; Wei LI; Weidong CHEN; Yu WANG (Meitan kexue jishu, 2024)
In order to explore the fracturing characteristics of coalbed methane wells in the Tunlan block, the No.2 coal seam in the Tunlan block, Xishan, Taiyuan was taken as the research object. The fracturing characteristics of the coal seams from multiple scales was studied through geological cataloguing, macroscopic characterization of coal samples and CT (Computed Tomography) analysis for four coal bed methane wells of XST-167, XST-168, XST-176 and XST-177, which were exposed at the coal mining face. The results shown that, the coal seam near the wells in the study area were mainly distributed with “X” type fractured fractures consisting of diagonally intersecting fractures, and there were “T” type fractured fractures near the XST-177 coalbed methane well. Collision and friction of quartz sand with fractured fracture walls produced pulverized coal, which filled in the fracture and hindered the output of coalbed methane. By comparing the drill holes exposed by the two coalbed methane wells of XST-168 and XST-177, it was found that the fracturing effect of the XST-177 coalbed methane well was better and more conductive to the output of coalbed methane. Most of the coals near coalbed methane wells were fragmented and crushed coal, and hydraulic fracturing destroyed the original structure of coal, which reduced the hardness of coal and significantly increased the cracks. Embedded quartz sand can be observed on some of the coal samples, which was mainly concentrated on the bedding surface, indicating that the quartz sand, after being pressed into the coal seam, mainly extended into the seam along the horizontal fracture, which was consistent with the direction of the maximum principal stress. By CT scanning technology, the coal samples affected by fracturing (fractured coal) and not affected by fracturing (normal coal) were scanned. It was found that, the fractures with a width greater than 100 μm in the fractured coals of T1 and T2 accounted for 58.8% and 48.5% of the total fracture volume, and the numbers of the fractures was 23407 and 19679, respectively. In normal coal T3, the fractures with width greater than 100 μm only accounted for 1.7% of the total fracture volume, and the number of fractures was only 3504. The width of the fractures in T1 and T2 was wider and the number of fractures was more than that in T3, which indicated that the width and number of fractures in the coal sample were significantly increased by the fracturing action, and the pores and fractures in the fractured coal were more developed.